Effect of Anodal Direct-Current Stimulation on Cortical Hemodynamic Responses With Laser-Speckle Contrast Imaging - Hu, Shuo; Zheng, Tao; Dong, Yanchao; Du, Juan; Liu, Lanxiang (Frontiers in Neuroscience, 2018)
Transcranial direct-current stimulation (DCS) offers a method for noninvasive neuromodulation usable in basic and clinical human neuroscience. Laser-speckle contrast imaging (LSCI), a powerful, low-cost method for obtaining images of dynamic systems, can detect regional blood-flow distributions with high spatial and temporal resolutions. Here, we used LSCI for measuring DCS-induced cerebral blood flow in real-time. Results showed that the change-rate of cerebral blood flow could reach approximately 10.1 ± 5.1% by DCS, indicating that DCS can increase cerebral blood flow and alter cortical hemodynamic responses. Thus, DCS shows potential for the clinical treatment and rehabilitation of ischemic strokes.